Ecotheology as a Media to Build Self-Awareness in the Student Learning Process - Nur Azizah; Lutfi Faishol (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing need for holistic education has highlighted the importance of fostering students’ self-awareness alongside cognitive achievement. However, educational practices often emphasize academic outcomes while paying limited attention to reflective, spiritual, and ecological dimensions of learning. This study aims to examine how ecotheology-based learning contributes to the development of students’ self-awareness during the learning process at MTs Pakis Cilongok, a madrasa located on the slopes of Mount Slamet, Central Java, Indonesia. The study employed a qualitative descriptive case study approach involving a school principal, teaching volunteers, and students selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and document analysis and were analyzed using thematic analysis. The findings reveal that the integration of ecotheological values into learning activities, including outdoor learning, observation and photography of local flora and fauna, nature reflection, and contextual practices such as coffee-processing activities, creates meaningful learning experiences that encourage self-reflection, responsibility, emotional regulation, and intrinsic motivation. Three major dimensions of students’ self-awareness emerged from the analysis: self-reflection, responsibility for learning, and spiritual meaning-making. Students increasingly perceived learning not only as an academic task but also as a process connected to personal growth, worship, and ecological responsibility. The study concludes that ecotheology-based learning functions as an effective psychopedagogical medium for fostering students’ self-awareness and supports the development of holistic, value-oriented, and sustainable educational practices within Islamic educational settings.